Preliminares (2017)
Este documento contiene en texto completo el articulo Preliminares publicado en "Universidad & Empresa" Journal; Vol. 19, Núm. 33 (2017): (julio-diciembre,0); 1-6;Universidad & Empresa; Vol. 19, Núm. 33 (2017): (julio-diciembre,0); 1-6;2145-4558;0124-4639;10.12804/revistas.urosario.edu.co/empresa/i.33